The Influence of Competency, SOP, and Information Technology on Employee Performance in Using the Ideaprocs Application in BUMD - Saepul Rizal; Amir Tengku Ramly; M. Aziz Firdaus; Nandang Sutisna; Rasiban Rasiban (Universitas KH. Abdul Chalim Mojokerto, 2025)
Human resources (HR) are very much needed in this increasingly advanced modern era, employees play an important role in running the system in the company which includes the company's vision, mission, and goals. HR also plans and acts actively in all Company functions related to technological progress and advancement. The purpose of this study is to analyze